Pengaruh Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER), dan Debt To Equity Ratio (DER) Terhadap Return Saham - Pangestu, Satrio Putro; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2020)
The technical and fundamental analysis is the solution by the investor to predict the stock price. Especially, this research discusses about the fundamental analysis by appraising the companies performance which is depicted on the companies financial report with ratio as tool to analyze the financial report. By using the financial ratio, it can be predicted by the investor about the companies condition, so that it would be a basis for the investors for choosing the companies that have a higher return level than the loss risks. The aim of this research are to test the influences of Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER), and Debt To Equity Ratio (DER) toward stock’s Return. The sampel in this research is the 13 companies that are listed on the sub-sectored stock in metal during the period of 2013-2017. Data analysis use the linier regression analysis with run SPSS 21.0. The result from this research shows that Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), Price Earning Ratio (PER), dan Debt To Equity Ratio (DER) have significant effect on the stock’s return. The independent variable simultaneously have significant effect on the stock’s return. As suggestion, the company should identified the assets that have a potential to support the companies procedure, optimize the modal’s usage, and optimize the debt management.